Determination of model characteristics of martial mixed arts fighters - Latyshev Sergii; Latyshev Mykola; Tsarevskaya Irina; Krivtsova Natalia; Ryzhin Nikolay; Nemceva Elena (E3S Web of Conferences, 2021)
The popularity of mixed martial arts(MMA) has been growing steadily and now this sport is the most striking and spectacular of martial arts. Worth millions royalties’ of top fighters stimulate talented athletes to change one types of martial arts for MMA, which significantly increase the competition among athletes and qualitatively change the competitive activity. A need arises to optimize the training process in accordance with modern trends in competitive activity. The process of training will be effective only if it is built on the basis of data on the model characteristics of today's top athletes. The article defined and calculated values of the model characteristics of Top MMA fighters of Ultimate Fighting Championship (UFC). These characteristics are divided into four groups: age-anthropometric, rating, kicks performance and defense, takedowns performance and defense. The obtained data can be used when planning the training process both for young and qualified sportsmen.